IMPLEMENTATION OF RELIGIUSITY AND LOCAL FUNCTION IN DEVELOPMENT OF OFFICE HUMAN RESOURCES MINISTRY OF RELIGION PALOPO CITY - Jabani, Muzayyanah; Takdir, Takdir (Universitas Islam Negeri Raden Fatah Palembang, 2020)
This study aims to determine whether the religiosity variable that focuses on the dimension of worship practices by discussing two aspects in it, namely obedience and rituals and local wisdom which consists of the culture of